PENGARUH KELAS GIZI BERBASIS POSITIVE DEVIANCE TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU IBU BALITA DI BAWAH GARIS MERAH (BGM) DI DESA MANTANG KECAMATAN BATUKLIANG KABUPATEN LOMBOK TENGAH - Abdul Salam; Suhaema Suhaema; Ni Ketut Sri Sulendri; Miftahul Jannah (Jurnal Kesehatan Prima, 2015)
Abstract: Background : The prevalence of malnutrition in West Nusa Tenggara Province is 30.5%, prevalence of underweight children under five in 2010 is 15.03%. The national target nutritional improvement in 2015 about prevalence of malnutrition by 10%. One effort to problem of malnutrition can by addressing the weight  toddler in the Lower Red Line (BGM) is the improvement of knowledge, attitudes and behavior of young children in terms of maternal health and nutrition, through positive deviance nutrition classes. Objective : To identify differences in knowledge, attitudes and behavior of the mother before and after the toddler BGM based nutrition classes in the village of positive deviance Mantang Batukliang Central Lombok District.Method : The Research is pre-experimental one group pretest posttest design without control. Partisipan/sample is mothers toddler BGM. Total sample of 25 people that using the cluster sampling. Data was collected the knowledge, attitudes and behavior mother of BGM toddler about nutrition which before and after class.  Data were analyzed using paired samples t-test.Results : Total of sample was 25 people, mostly 20-35 years old,  work as a housewife. The average 57.1% of initial knowledge, attitudes 63.7% and behaviors 57.6%, after follow knowledge of nutrition classes increased to 60.9%, 65.9% attitude and behavior of 58.4%. The statistic analisys demonstrate  the knowledge, attitudes and behaviors increase before and after classes with significant nutritional value of p = 0.000, p = 0.003 and  p = 0.016.